El Excentrico, 1961-10-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
October 20, 1961 [20 de octubre de 1961]. Ano 12, No 01. Cover has a photograph of a people in costume celebrating a Halloween party. This cover was advertising a Halloween Dance that was hosted by the Club Bachelor's and Elite. This event took place in October 27th at 9:00 PM at the I.E.S. Hall.